To the Nations for the Earth: A Missional Spirituality - Wim, Chandra (Sekolah Tinggi Teologi SAAT, 2020)
In the last two or three decades, we have witnessed a renewed interest in spirituality in Christian academic circles. More recently, we have also seen a growing number of publications on the mission and missional church—both on popular and academic levels. While one can easily find many quality works on Christian spirituality and some decent books on mission/missional church, one would only find a few works that combine both themes in a single volume. In this work, Charles Fensham, professor of theology at Knox College, Toronto, attempts to do just that—as one may discern from the book’s subtitle: A Missional Spirituality. As such, this book addresses those who have interest in spirituality and/or in mission but particularly to those who would like to see how biblical missional impetus shapes a particular understanding of Christian spirituality.